2010
DOI: 10.3109/0142159x.2011.530314
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interprofessional education on patient perceived quality of care

Abstract: Patients perceived a higher grade of quality of care as compared to controls with no signs of disadvantages when treated and informed by supervised interprofessional student teams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 11 publications
6
80
0
3
Order By: Relevance
“…Thistlethwaite (2012) has argued ''there is a need for educators to define learning outcomes and match these with learning activities to ensure that IPE demonstrates added value'' (p. 58). Encouragingly, reports are beginning to emerge documenting positive impact on patient-perceived quality of care following IPE clinical education (Hallin, Henriksson, Dalen, & Kiessling, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thistlethwaite (2012) has argued ''there is a need for educators to define learning outcomes and match these with learning activities to ensure that IPE demonstrates added value'' (p. 58). Encouragingly, reports are beginning to emerge documenting positive impact on patient-perceived quality of care following IPE clinical education (Hallin, Henriksson, Dalen, & Kiessling, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The answer to that question appears to be interprofessional education (IPE), defined as "two or more professions learn from, with and about each other to improve collaboration and quality of care" (3). Despite this emphasis on IPE as a mechanism to improve IPC, there has been minimal conclusive evidence tying improved clinical outcomes to IPE interventions (4,6).…”
Section: Introductionmentioning
confidence: 99%
“…Howkins and Bray (2008) reported that interprofessional education (IPE) improves students' learning experiences and optimizes patient treatment. Hallin et al (2011) found that patients who received treatment from interprofessionally educated clinical teams, perceived and rated quality of treatment and care significantly higher compared to usual care by regular staff.…”
Section: Literature Reviewmentioning
confidence: 99%